2021
DOI: 10.4081/ejtm.2021.9642
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between muscular fitness and bone health in young baseball players

Abstract: The physical actions developed by baseball players can increase muscular fitness, and consequently improve bone health. The objective was to relate some indicators of muscular fitness to bone health in young baseball players. A descriptive cross-sectional study was carried out in 102 children and adolescent baseball players of the Brazilian National Team. The age range ranged from 9.0 to 15.0 years, the average chronological age was 12.2±2.2 years and the maturity status was 14.8±0.5 APHV (age at peak height v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In fact, since the publication of the study by Mirwald et al [18], in which the BSA prediction equation is proposed in both sexes, more than 20 years have elapsed, in which it has been widely used in school [5,22,23] and sports populations [24,25,26]. Even, the same study group using the same database, made an adjustment to the initial equations, in which seated height was eliminated, and published new equations with a lower prediction error (known as Moore equations).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, since the publication of the study by Mirwald et al [18], in which the BSA prediction equation is proposed in both sexes, more than 20 years have elapsed, in which it has been widely used in school [5,22,23] and sports populations [24,25,26]. Even, the same study group using the same database, made an adjustment to the initial equations, in which seated height was eliminated, and published new equations with a lower prediction error (known as Moore equations).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, it was concluded that high physical activity weakens this association. However, there are many studies reporting a relationship between muscle strength and BMD 23 , 24 . These conflicting results may be due to individual differences in athletes and training protocols.…”
Section: Discussionmentioning
confidence: 99%